An adaptive approach to blockchain in smart system applications - Alsadi N; Giuliano A; Gadsden SA; Yawney J (My University, 2023)
As the technological landscape continues rapidly evolving, blockchain technology has been widely integrated and employed in various areas of application. Blockchain, at its core, offers a decentralized method for system security and communication. This is in contrast with classical security systems, which necessitate a central node for data processing and communication, therefore augmenting vulnerability to a single point of failure and attack. Incorporating adaptive subsystems into various blockchain technology features might greatly enhance their functionality without jeopardizing the chain’s immutability. Several publications have focused on the analysis of network node data in an effort to offer an adaptive version of the consensus mechanism used in the blockchain process. This paper presents a novel adaptive consensus mechanism that regulates the Proof-of-Work mining difficulty based on the perceived anomalous level of network nodes.
Keywords: 40 Engineering; 4006 Communications Engineering; 4009 Electronics, Sensors and Digital Hardware; 51 Physical Sciences; 5102 Atomic, Molecular and Optical Physics